Characteristics of atherosclerosis in femoropopliteal artery and its clinical relevance. (October 2021) - Poredoš, Pavel; Cevc, Matija; Blinc, Aleš
Abstract: Atherosclerosis is a systemic disease with different faces. Despite identical or similar pathogenetic mechanisms, atherosclerotic lesions and their clinical manifestations vary in different parts of the vascular system. Peripheral arterial disease (PAD) represents one of the most frequent clinical manifestations of atherosclerosis with predominant location in the superficial femoral artery (SFA). Morphological characteristics of atherosclerotic plaques in peripheral arteries differ from lesions in the coronary and carotid arteries. Plaques in SFA have more fibrotic components, less lipids and inflammatory cells, which makes them more stable and less prone to rupture. Factors that determine the different structure of plaques in SFA compared to coronary arteries include hemodynamic forces, vasa vasorum and calcification. Low shear stress in SFA in the adductor canal is one of the factors which determines frequent atherosclerotic lesions in this region. Lower lipid content and fewer inflammatory cells explain higher stability of SFA plaques. The specific structure of SFA plaques may require preventive and therapeutic measures, which to some extent differ from prevention of coronary atherosclerosis and may include inhibition of fibrotic proliferation in SFA plaques and calcification. Revascularization of PAD differs from procedures used in coronary arteries and requires specific technical expertise and devices. Graphical abstract: Image 1 Highlights: The atherosclerotic plaque structure of the superficial femoral artery (SFA) differs from plaque in other territories. Plaques in SFA have more fibrotic components, and smooth muscle cells, less inflammatory cells and lipids. They are more stable. Low shear stress and low density of vasa vasorum influence plaque structure in SFA, which differs from coronary arteries. The growth of plaque in SFA is slower and relates to less thrombotic complications. Different plaque structures in SFA may provoke different therapeutic measures e.g. inhibition of fibrotic proliferation.